Fraud analysis in micro finance institution - Silviana Pebruary; M. Yunies Edward; Eko Nur Fuad; H. Ardian Adhiatma; Widiyanto Widiyanto (Faculty of Economics, Universitas Islam Indonesia, 2019)
Islamic microfinance institutions are financial institutions that carry out operational activities based on sharia principles. One of them is the Baitul Maal wa Tamwil (BMT), this institution serves savings and funding to the middle and lower communities by picking up the ball. With this system, it will be an opportunity for human resources (SDI) who are less loyal and responsible with their institutions to commit fraud or irregularities. Therefore, this study aims to find out how triangle fraud affects the occurrence of fraud in BMT. The research method uses independent path analysis with a sample of 84 respondents from the marketing department, supervisors, and financing managers. The results of this study are that Rationalization and pressure have a positive and significant effect on the occurrence of fraud, while the opportunity does not have an influence on the occurrence of fraud.